Emotional Marketing and Forced Inclusion: Impact on Peruvian Millennial and Centennial Users in Audiovisuals - Gayla Ivanna Fajardo Ronceros; Sharon Raquel Tacanga Camasca; Africa Calanchez Urribarri (Telos: Revista de Estudios Interdisciplinarios en Ciencias Sociales)
One of the strategies used in the audiovisual industry is emotional marketing, which seeks to connect deeply with the audience through their emotions and memories. However, a poor execution of this strategy may lead to controversial associations with a brand. A controversial phenomenon has emerged within the industry, perceived in audiovisual content by millennial and centennial consumers, referred to as Forced Inclusion. The purpose of this study is to analyze the impact of emotional marketing and forced inclusion on millennials and centennials in modern Lima within the audiovisual industry. A qualitative approach was used, with data collection through interviews, involving 20 participants. The findings reveal that the majority of participants agree that they perceive greater progress and awareness of diversity in audiovisual industry products; however, both generations perceive that forced inclusion is positioned as a set of actions driven by economic convenience. This creates an unfavorable impression of the product when the actions carried out by the industry exceed the normative, moral, and cultural limits of a given social group; thus, emotional marketing is crucial for improving the brand’s perception in relation to this phenomenon. This study encourages further research not only focused on such a limited segment but also on global audiences. Additionally, it advocates for companies to develop better inclusion strategies that reflect genuine social values in the audiovisual industry.